Activism in the age of mediated communication: The impact of new media on the development of activist movements - Miguel, A.; Miranda, S. (El poder de la comunicación actores, estrategias y alternativas, 2022)
The emergence and expansion of new digital media led to profound economic, cultural, political and social transformations, which not only changed the relationship between media and audiences but also had a strong impact on the dissemination and organization of broader social phenomena, such as activist movements. New interactive technologies and their use by the common citizen have strongly intensified globalization, led to the decentralization of geopolitical authorities, provided large-scale two-way communication, expanded cultural circulation, reduced barriers between private and public issues, and brought greater opportunities for civic expression. The potentialities of new media thus led to profound changes in the behavior of the public, which, by starting to participate in communication exchanges, today assumes the role of Produser, becoming both a producer, receiver and user of online content. This new type of public, with bigger power to contribute and influence the attitudes of others in relation to the most diverse subjects, began to use the new media to group themselves in multiple “virtual communities” with greater capacity to initiate or strengthen social movements on a global scale, as they can communicate and share their ideals worldwide and, consequently, can more easily place these issues on the public agenda. In this way, digital media gave greater power of expression to activist movements and influenced the methods by which these movements are prepared and implemented. If initially activist movements were processed through direct actions, such as protests, demonstrations, boycotts or civil disobedience, since the 1990s there has been a growing debate about activism practices on the Internet - the so-called Cyberactivism - and how new media can be used by a variety of sociopolitical movements. However, the possibility of communicating and establishing activist practices mediated by digital technologies brings several advantages, but also challenges, for the communication of these social movements, derived from the inequality of access and use of technology, from the economic, social and political context in that the use of this technology occurs, the nature of transience of digital platforms and the information overload that often occurs on it. This theoretical investigation will explore how the new media contributed to the propagation of activist movements and how it came to shape the practices of these social movements, in addition to highlighting and debating the benefits and risks that mediated communication brought to activism. Based on a literature review and concrete examples, an overview of current cyberactivism practices will be presented, as well as the media transformations and evolutions that led to the development of these social movements and to broader notions of citizenship. In addition, the benefits and risks of digitally mediated communication in terms of activism will be discussed, adopting a critical view of how activist movements can gain power, but also be obstructed, in cyberspace. Finally, the investigation will conclude on the importance of adopting a holistic approach between online and offline as a way of not distorting activist militancy and effectively promoting new models of civic engagement and participation.